Empire and environment : ecological ruin in the Transpacific - Santa Ana, Jeffrey, 1965-; Amin-Hong, Heidi, 1990-; Chua, Rina Garcia; Zhou, Xiaojing, 1952- (University of Michigan Press, 2022)
"Empire and Environment argues that histories of imperialism, colonialism, militarism, and global capitalism are integral to understanding environmental violence in the transpacific region. The collection draws its rationale from the imbrication of imperialism and global environmental crisis, but its inspiration from the ecological work of activists, artists, and intellectuals across the transpacific region. Taking a postcolonial, ecocritical approach to confronting ecological ruin in an age of ecological crises and environmental catastrophes on a global scale, the collection demonstrates how Asian North American, Asian diasporic, and Indigenous Pacific Island cultural expressions critique a de-historicized sense of place, attachment, and belonging. In addition to its thirteen body chapters from scholars who span the Pacific, each part of this volume begins with a poem by Craig Santos Perez. The volume also features a foreword by Macarena Gómez-Barris and an afterword by Priscilla Wald"--